Polypropylene Nanofibers Melt Electrospinning Versus Meltblowing - Nayak, Rajkishore; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comparison between melt electrospinning and meltblowing as techniques for the production of polypropylene nanofibers. The author compares the morphological, structural, chemical and mechanical characteristics of the different produced fibers. Moreover, the degree of thermal degradation of the different fibers is also analyzed. The book is useful to chemists and material scientists working on the synthesis of nanofibers by melt processes, showing the limitations of each technique for nanofiber fabrication.
Introduction -- Review of the literature on Melt Electrospinning -- Production of Polypropylene Nanofibers by Melt Electrospinning -- Review of the literature on Meltblowing -- Production of Polypropylene Nanofibers by Meltblowing -- Comparing both techniques -- Outlook.
Keywords: Nanotechnology; Optical materials; Materials -- Analysis; Nanotechnology; Optical Materials; Characterization and Analytical Technique